Host preference of the pulse beetle (Callosobruchus chinensis L.) on different pulses (The Journal of Plant Protection Sciences, 2024)
Pulses are important source of plant protein in  many developing countries of the tropics and  sub-tropics and considered as the second most  important group of crops worldwide. Glob ally, 840 million people are undernourished  mainly on account of inadequate intake of  proteins, vitamins and minerals in their diets.  Out of total 12.6 million tons, 5.5% is lost due  to the non-availability of proper storage facili ties with the farmers and vulnerability of  pulses to stored grain pests (4) which inflict  severe losses mainly in the storage. Among  the storage pests, bruchids particularly the  pulse beetle, Callosobruchus chinensis L. in cur greater importance as the pest having cos mopolitan distribution and causing serious  damage to pulses from the field (5).
Keywords: generation; inadequate; undernourished